THE RELEVANCE OF TEACHING METHODS AND TECHNIQUES AND THE PROBLEMS OF INTRODUCING INNOVATIVE TEACHING METHODS - Dilorom Xoshimova (Journals Park Publishing, 2025)
This article is devoted to the analysis of the problems of the process of updating methods and methods of teaching and the introduction of innovative teaching methods in the education system of Uzbekistan. To achieve high results in modern education, it is important to improve the pedagogical skills of teachers, introduce digital technologies into the educational process, introduce interactive and innovative methods difficulties, in particular, with technical and resource constraints.
Keywords: Learning methods, innavigation tmethods of teaching, education system of Uzbekistan, digital technologies, pedagogical qualifications, reforms, educational infrastructure, pedagogy, preservation, competition, education.